Kıbrıs’ta Sultan Murad Han’ın Validesine (Kösem Sultan) Ait Mülk Çiftlikler - Dündar, Recep (Karadenīz araştırmaları, 2012)
Abstract The Detailed Census Book no 64 which contains the first census records of Cyprus Province is found in the archives of the General Directorate of Land Registry and Cadastre. The farm records that are the subject of our study were added much later into the Book between the Baf and the Evdim district records. In the records of Kukla, Mamonya, Aselli and Bodime farms that belonged to the mother of Sultan Murad Han, the names of the fields in the farms, their size and their borders are stated. Total number of fields and their size are also given at the end of each farm record. The number and size of the fields that belonged to the farms are calculated and their total amount is given at the end of the document. The Kukla farm is 1461000 square metres containing 34 fields, the Mamonya farm is 564000 square metres containing 14 fields, the Aselliye farm is 5517000 square metres containing 26 fields and the Bodime farm is 289000 square metres containing 15 fields.